2016
DOI: 10.3389/fmicb.2016.01160
|View full text |Cite
|
Sign up to set email alerts
|

Flavoprotein-Mediated Tellurite Reduction: Structural Basis and Applications to the Synthesis of Tellurium-Containing Nanostructures

Abstract: The tellurium oxyanion tellurite (TeO32-) is extremely harmful for most organisms. It has been suggested that a potential bacterial tellurite resistance mechanism would consist of an enzymatic, NAD(P)H-dependent, reduction to the less toxic form elemental tellurium (Te0). To date, a number of enzymes such as catalase, type II NADH dehydrogenase and terminal oxidases from the electron transport chain, nitrate reductases, and dihydrolipoamide dehydrogenase (E3), among others, have been shown to display tellurite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 87 publications
(105 reference statements)
0
29
1
Order By: Relevance
“…Psychrophilic and psychrotolerant microorganisms require several genes to increase their phenotypic flexibility to survive in extreme environments such as cold habitats. Thus, in addition to genes associated with cold shock proteins, membrane fluidity, among others, the presence of metal(loid) resistance genes seems to favor their adaptation (Dziewit and Bartosik, 2014;Rodríguez-Rojas et al, 2016). This is also the case of P. glacincola BNF20, which harbors over 100 putative metal resistance genes (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Psychrophilic and psychrotolerant microorganisms require several genes to increase their phenotypic flexibility to survive in extreme environments such as cold habitats. Thus, in addition to genes associated with cold shock proteins, membrane fluidity, among others, the presence of metal(loid) resistance genes seems to favor their adaptation (Dziewit and Bartosik, 2014;Rodríguez-Rojas et al, 2016). This is also the case of P. glacincola BNF20, which harbors over 100 putative metal resistance genes (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Some of the genes implicated in tellurite resistance include trgAB from Rhodobacter sphaeroides (unknown function, encoding likely membrane-associated proteins) (O´Gara et al, 1997), tmp from Pseudomonas syringae (encoding a thiopurine methyltransferase, involved in tellurium alkylation) (Prigent-Combaret et al, 2012), lpdA from Aeromonas caviae ST (encoding dihydrolipoamide dehydrogenase, involved in tellurite reduction) (Castro et al, 2008) and gor from Pseudomonas sp. (encoding glutathione reductase, involved in tellurite reduction) (Arenas et al, 2016;Pugin et al, 2014). Tellurite resistance genes were also identified in the ter operon (terZABCDEF) from Escherichia coli and other pathogenic species (Taylor, 1999;Whelan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Metal(loid) reduction by microbial systems could be of great help in decontaminating soluble metal ions from soils, forming insoluble, less-toxic derivatives that often generate metal arrangements at the nanoscale (Narayanan and Sakthivel, 2010 ; Thakkar et al, 2010 ), also known as nanostructures (NS) exhibiting one or more dimensions <100 nm. Gold (Correa-Llantén et al, 2013 ), selenium (Song et al, 2017 ), silver (Gurunathan et al, 2009 ), tellurium (Arenas-Salinas et al, 2016 ), and uranium (Suresh, 2012 ) NS have been reported, opening a great interest because of their potential application in the field of biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…A number of flavoproteins able of metal ion reduction to less toxic, insoluble forms have been described, including (i) mercury reductase (MerA) (Silver and Phung, 2005 ), (ii) glutathione reductase (Au 3+ and reduction, Pugin et al, 2014 ), (iii) fumarate reductase (selenite reduction, Song et al, 2017 ), (iv) thioredoxin reductase and alkyl hydroperoxide reductase that reduce tellurite (Arenas-Salinas et al, 2016 ) and (v) nitrate reductase, able to reduce tellurite as well as silver (Kumar et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genes implicated in tellurite resistance include trgAB from Rhodobacter sphaeroides (unknown function, encoding likely membrane-associated proteins) ( O’Gara, Gomelsky & Kaplan, 1997 ), tmp from Pseudomonas syringae (encoding a thiopurine methyltransferase, involved in tellurium alkylation) ( Prigent-Combaret et al, 2012 ), lpdA from Aeromonas caviae ST (encoding dihydrolipoamide dehydrogenase, involved in tellurite reduction) ( Castro et al, 2008 ) and gor from Pseudomonas sp. (encoding glutathione reductase, involved in tellurite reduction) ( Arenas et al, 2016 ; Pugin et al, 2014 ). Tellurite resistance genes were also identified in the ter operon ( terZABCDEF ) from Escherichia coli and other pathogenic species ( Taylor, 1999 ; Whelan, Sherburne & Taylor, 1997 ).…”
Section: Introductionmentioning
confidence: 99%